Interaction of shikimic acid with shikimate kinase (Retracted Article. See vol 334, pg 967, 2005) - Pereira, J. H.; de Oliveira, J. S.; Canduri, F.; Dias, MVB; Palma, Mario Sergio [UNESP]; Basso, L. A.; de Azevedo, W. F.; Santos, D. S. (Elsevier B.V., 2004)
The crystal structure of shikimate kinase from Mycobacterium tuberculosis (MtSK) complexed with MgADP and shikimic acid (shikimate) has been determined at 2.3 Angstrom resolution, clearly revealing the amino acid residues involved in shikimate binding. In MtSK, the Glu61 strictly conserved in SK forms a hydrogen bond and salt-bridge with Arg58 and assists in positioning the guanidinium group of Arg58 for shikimate binding. The carboxyl group of shikimate interacts with Arg58, Gly81, and Arg136, and hydroxyl groups with Asp34 and Gly80. The crystal structure of MtSK-MgADP-shikimate will provide crucial information for elucidation of the mechanism of SK-catalyzed reaction and for the development of a new generation of drugs against tuberculosis. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: drug design; Mycobacterium tuberculosis; shikimate kinase; Structure; shikimic acid